2009
DOI: 10.1016/j.scr.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of the colony-forming units–fibroblast from mouse and human bone marrow in normal and pathological conditions

Abstract: Bone marrow stromal cell populations, containing a subset of multipotential skeletal stem cells, are increasingly contemplated for use in tissue engineering and stem cell therapy, whereas their involvement in the pathogenetic mechanisms of skeletal disorders is far less recognized. We compared the concentrations of stromal clonogenic cells, colony forming units–fibroblast (CFU-Fs), in norm and pathology. Initially, culture conditions were optimized by demonstrating that fetal bovine serum heat inactivation cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 87 publications
7
57
0
2
Order By: Relevance
“…Isolation and characterization of murine ABCG2 + lung MPCs paralleled our findings in the in vivo models and in human MPC lines. Both Bmpr2 fl/+ and βOE ABCG2 + murine lung MPCs showed a decreased ability to form CFU-F, which is indicative of a loss of functional clonogenic progenitors (Supplemental Figure 4B) (27). We observed that the loss of clonogenic potential paralleled an increase in pericyte lineage specification compared with WT MPCs, keeping in mind that lineage specification is not equal to terminal differentiation into mature and functional contractile pericytes (28,29).…”
Section: Resultsmentioning
confidence: 61%
“…Isolation and characterization of murine ABCG2 + lung MPCs paralleled our findings in the in vivo models and in human MPC lines. Both Bmpr2 fl/+ and βOE ABCG2 + murine lung MPCs showed a decreased ability to form CFU-F, which is indicative of a loss of functional clonogenic progenitors (Supplemental Figure 4B) (27). We observed that the loss of clonogenic potential paralleled an increase in pericyte lineage specification compared with WT MPCs, keeping in mind that lineage specification is not equal to terminal differentiation into mature and functional contractile pericytes (28,29).…”
Section: Resultsmentioning
confidence: 61%
“…by guest www.bloodjournal.org From perivascular location, 32,33,41 little is currently known about the molecular composition of the niche occupied by CFU-F in the BM in vivo, but these findings would suggest that stromal progenitors, like hematopoietic stem cells, 42 occupy a hypoxic microenvironment. It should also be noted that the high plating efficiency of CFU-F demonstrated in these studies is occurring in the absence of exogenous mitogenic growth factors, such as FGF2 or feeder cells shown in previous reports, 13,23,24 to be necessary for optimal CFE of CFU-F from mouse BM. Our data in no way exclude a role for accessory cells and their products in promoting the growth of CFU-F, and it will be of interest to determine whether the CFE reported here can be further improved after addition of feeder cells and/or growth factors and, moreover, to define the requirements of CFU-F isolated using the new methodology for growth in serum-free conditions.…”
Section: Isolation Of Mouse Bm Stromal-vascular Fraction E93mentioning
confidence: 59%
“…Reported incidences of CFU-F are typically in the range of 0.3 to 2 per 1 000 000 13,18,22 BM cells in C57BL/6 mice. Significant increases in the frequency of CFU-F (range, 35-115 of 1 000 000) have been demonstrated either by the use of irradiated feeder cells 23 or after mechanical dissociation of the BM followed by trypsin digestion of remaining clumps, as described by Freidenstein et al 24 These methodologic improvements notwithstanding, the low incidence of CFU-F is a significant impediment to the isolation of murine BMSC populations using the standard method of plastic adherence, a common problem being contamination with hematopoietic cells, particularly macrophages. Although the contaminating hematopoietic cells are reduced by frequent and prolonged subculturing, this strategy comes with the attendant risk of proliferative exhaustion of the low numbers of founding progenitors typically used to initiate BMSC cultures from mouse BM, together with the possibility of altered differentiation or, at the other extreme, spontaneous transformation, which has been reported after long-term in vitro culture of mouse BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this study, the number of adipocytic colonies followed a similar pattern, suggesting a general atrophy of MSC. Human studies also revealed variable results with some studies showing age-related decrease in the number of CFU-f (Nishida et al, 1999;Stolzing et al, 2008;Kuznetsov et al, 2009) or no change (Oreffo et al, 1998;Stenderup et al, 2001). Also, the number of Stro-1+ (a marker of the clonogenic CFU-F) did not change with age (Stenderup et al, 2001;Zhou et al, 2008).…”
Section: Age-related Skeletal Stem Cell Atrophymentioning
confidence: 99%